Patrimoine carcéral et médiation scientifique : le cas de la prison Jacques-Cartier (Rennes) - Fanny Le Bonhomme; Gaïd Andro (Criminocorpus)
This article aims to question the possibilities of patrimonialization of the Jacques Cartier prison in Rennes, an architectural space that is both ordinary and exceptional in French prison history, which closed its doors in 2010. The exceptional conservation of this building and its purchase by the city provide an unprecedented opportunity to think about a reconversion of the prison that would link scientific research and society, while questioning the place of this "dark heritage" in the urban imagination of Rennes. By analyzing the first months of the conversion project led by the city and by questioning the place of social sciences - especially history - in this process, this article considers the Jacques-Cartier prison as an opportunity to conceive a possible place of mediation between scientific research and the citizen space in a concerted and co-constructed process. In this reflexive and pragmatic proposal, the place of prison history in the common history and the definition of this place in the urban space are necessarily thought in resonance.